1952
DOI: 10.4039/ent84113-4
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Various Food Plants on Melanoplus mexicanus mexicanus (Sauss.) (Orthoptera: Acrididae)

Abstract: The long-held belief that grasshoppers are to a large extent omnivorous and, as Wolcott (1936) states, “like cows, feed on any kind of vegetation”, is slowly giving place to the view that they are much more restricted feeders. Their habit of nibbling at almost anything, particularly when they are present in large numbers, probably led to this erroneous concept. More recent work such as that of Rubtzov (1931), Criddle (1933), and Isely (1938, 1944, 1916) stresses the fact that many species of grasshopper confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1959
1959
2000
2000

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Parker (1930) recorded one caged female which laid 15 egg pods, and the average for 30 females observed by him was 8.8 pods. Other data on egg production were presented by Pfadt (1949) and Smith, Handford, and Chefurka (1952). In laboratory cages, using material from central Saskatchewan, Pickford (Shotwell, 1930, p. 23) and the location.…”
Section: )mentioning
confidence: 99%
“…Parker (1930) recorded one caged female which laid 15 egg pods, and the average for 30 females observed by him was 8.8 pods. Other data on egg production were presented by Pfadt (1949) and Smith, Handford, and Chefurka (1952). In laboratory cages, using material from central Saskatchewan, Pickford (Shotwell, 1930, p. 23) and the location.…”
Section: )mentioning
confidence: 99%
“…Such plants may have provided both moisture and the necessary requirements for oviposition and food, although Smith et al (1952) and Pickford (1962) demonstrated that M. sanguinipes survived poorly and produced few egg pods if S. kali was the only food. sangztinipes laid its eggs qenerally throughout the fields, but more eggs were found on drift ridges at the k e~d margins, particularly on the warmer slopes facing south and west.…”
Section: Discussionmentioning
confidence: 99%
“…Survival was highest and nymphal developmental rates fastest when Melanoplus sanguinipes (Fabricius) and Camnula pellucida Scudder were provided a straight or mixed diet of winter wheat (Triticum aestivium L.) or Hordeum vulgare L. and weeds as opposed to western wheatgrass (Agropyron smithii Rydb.) (Pfadt 1949;Smith et al 1952;Pickford 1958Pickford , 1962Pickford , 1963Reigert et al 1965). In similar studies both species experienced poorer survival and slower developmental rates on diets composed exclusively of native plants versus those fed a combination of wheat and weeds (Putnam 1962;Pickford 1963).…”
Section: Introductionmentioning
confidence: 99%